GRIT Guru PAUD ditinjau dari peran kepribadian playfulness dan playful work design - Savitri, Setiawati Intan; Widyaningsih, Murni (Jurnal Konseling dan Pendidikan, 2024)
In-depth ongoing research has explained that a person's Grit is influenced by consistency of interest and persistence. However, not many have examined whether there are other factors that can contribute to increasing Grit. . To measure Grit, we used the Indonesian version of Teacher Grit Scale (TGS), then to measure the level of Playfulness, we used Adult Playfulness Trait Scale (APTS), and Playful Work Design (PWD) scale was used to measure the level of Playful Work Design.We use predictive-correlational designed, with statistical analysis using multiple linear regression techniques using SPSS IBM version 25. The findings shows   Playfulness personality and Playful Work Design simultaneously predict Grit in early childhood teachers. Playfulness and Playful Work Design provide an influence on Grit by 29.8%, while the other influence of 70.2% comes from other factors not examined in this research. The results of this research show that a playful personality alone is not enough, but must be accompanied by cognitive abilities to design oneself and the environment to be playful, in order to significantly influence PAUD Teacher Grit